WS2 Nanoparticles: Bipolar Electrochemical Synthesis of WS2 Nanoparticles and Their Application in Magneto‐Immunosandwich Assay (Adv. Funct. Mater. 23/2016). (20th June 2016) - Mayorga‐Martinez, Carmen C.; Khezri, Bahareh; Eng, Alex Yong Sheng; Sofer, Zdeněk; Ulbrich, Pavel; Pumera, Martin
Abstract : M. Pumera and co‐workers synthesized layered WS2 nanoparticles by bipolar electrochemistry by applying potential bias across two electrodes as described on page 4094. The obtained nanoparticles are successfully used as a label in a standard magneto‐immuno sandwich assay for protein detection through the hydrogen evolution reaction. The method offers a low cost approach to WS2 as sensor material in numerous biomedical applications.